Reducing the Inconsistency between Doppler and Invasive Measurements of the Severity of Aortic Stenosis Using Aortic Valve Coefficient: A Retrospective Study on Humans. (28th May 2014) - Paul, Anup K.; Banerjee, Rupak K.; Narayanan, Arumugam; Effat, Mohamed A.; Paquin, Jason J.
Abstract : Background . It is not uncommon to observe inconsistencies in the diagnostic parameters derived from Doppler and catheterization measurements for assessing the severity of aortic stenosis (AS) which can result in suboptimal clinical decisions. In this pilot study, we investigate the possibility of improving the concordance between Doppler and catheter assessment of AS severity using the functional diagnostic parameter called aortic valve coefficient (AVC), defined as the ratio of the transvalvular pressure drop to the proximal dynamic pressure. Method and Results . AVC was calculated using diagnostic parameters obtained from retrospective chart reviews. AVC values were calculated independently from cardiac catheterization (AVC c a t h e t e r ) and Doppler measurements (AVC d o p p l e r ). An improved significant correlation was observed between Doppler and catheter derived AVC (r = 0.92, P < 0.05 ) when compared to the correlation between Doppler and catheter measurements of mean pressure gradient (r = 0.72, P < 0.05 ) and aortic valve area (r = 0.64, P < 0.05 ). The correlation between Doppler and catheter derived AVC exhibited a marginal improvement over the correlation between Doppler and catheter derived aortic valve resistance (r = 0.89, P < 0.05 ). Conclusion . AVC is a refined clinical parameter that can improve the concordance between the noninvasive and invasive measures of the severity of aortic stenosis.